Silicon Fertilization: A Step towards Cadmium-Free Fragrant Rice - Qamar uz Zaman; Muhammad Rashid; Rab Nawaz; Afzal Hussain; Kamran Ashraf; Maria Latif; Abdihakim Osman Heile; Faisal Mehmood; Sughra Salahuddin; Yinglong Chen (Plants, 2021)
Soil contamination with toxic cadmium (Cd) is becoming a serious global problem and poses a key hazard to environments and the health of human beings worldwide. The present study investigated the effects of foliar applications of three forms of silicate chemicals (calcium silicate, sodium silicate, and potassium silicate) at four rates (0.25%, 0.5%, 0.75%, and 1.0%) at tillering stage on rice growth and the accumulation of Cd under Cd stress (30 mg kg−1). The results showed that Cd stress reduced the yield-related traits and enlarged Cd contents in different rice organs. The leaf gas exchange attributes and yield traits were enhanced, and the Cd accumulation and bioaccumulation factor in rice organs were reduced, especially in grains, through silicon application. In shoots, roots, and grains, foliar spray of Si reduced Cd contents by 40.3%, 50.7%, and 47.9%, respectively. The effectiveness of silicate compounds in reducing Cd toxicity varied with the kind of chemicals and doses of foliar applications. Foliar application of potassium silicate, at a rate of 0.5%, at tillering stage, showed the best effectiveness in improving grain yield, while mitigating Cd accumulation in rice grains. The outcome of this study provides a promising practicable approach in alleviating Cd toxicity in rice and preventing the entrance of Cd into the food chain.